مساهمة استراتيجية تسيير الموارد البشرية في زيادة أداء المؤسسات الاقتصادية - منصور, مليكة; خالف, كاتبة (جامعة الوادي University of Eloued, 2021)
تهدف دراستنا الى معرفة كيف تساهم استراتيجية تسيير الموارد البشرية في زيادة أداء المؤسسات الاقتصادية بمختلف الآليات التي تتوفر عند وضع مبادئ في تسيير الموارد البشرية مبنية على الإستراتيجية، حيث تعمل المؤسسات عامة والاقتصادية خاصة على تحقيق أحسن أداء في مختلف نشاطاتها الذي يضمن لها أكبر قدر ممكن من العوائد والمنافع الاقتصادية الذي من خلاله تحافظ على مكانتها في السوق من خلال التنافسية المتميزة التي حققها الأداء الجيد، حيث لا يتأتى كل ما سبق ما لم يكون للمؤسسة مورد بشري كفئ يستجيب ومتطلبات أهداف المؤسسة، ولا يتوفر هذا المورد البشري ما لم تعمل المؤسسة على وضع إستراتيجية فعالة لتسيير الموارد البشرية مبنية على أسس علمية وعملية، كالتدريب والتكوين والتمكين ونظم المعلومات البشرية، والتوظيف ......الخ. Our study aims to establish the way human ressources strategy contributes in the increase of performance of economic institutions through various mechanisms that are based on that strategy where public and economic institutions work on achieving the best performance in their various activities to ensure the greatest possible revenues and economic benefits which maintain its position in the market through the competitiveness achieved by good performance. All of the above will not be achieved unless the institution has a talented human resource which responds to the requirements of the institution’s objectives. In order to obtain such a human resourcethe institution must put in place an effective strategy to manage them based on scientifical and practical foundations such asࢫ،training formingࢫ،empoweringࢫ ،human information system and employment....etc
The Contribution of Human Resources Management Strategy To Increasing the Performance of Economic Institutions
مقال
Keywords: الاستراتيجية، التسيير الاستراتيجي، الأداء، تسيير المورد البشري، الإدارة الإستراتيجية للموارد البشرية; Strategic management; Performance; Human resource management; Strategic management of human resources.